Clinical characteristics and outcomes of patients with adult congenital heart disease listed for heart and heart‒lung transplantation in the Eurotransplant region - Becher, Peter Moritz; Schrage, Benedikt; Weimann, Jessica; Smits, Jacqueline; Magnussen, Christina; Reichenspurner, Hermann; Goßling, Alina; Rodrigus, Inez; Dumfarth, Julia; de Pauw, Michel; François, Katrien; van Caenegem, Olivier; et al. (The journal of heart and lung transplantation, 2020)
BACKGROUND - The therapeutic success in patients with congenital heart disease (CHD) leads to a growing number of adults with CHD (adult CHD [ACHD]) who develop end-stage heart failure. We aimed to determine patient characteristics and outcomes of ACHD listed for heart transplantation. - METHODS - Using data from all the patients with ACHD in 20 transplant centers in the Eurotransplant region from 1999 to 2015, we analyzed patient characteristics, waiting list, and post-transplantation outcomes. - RESULTS - A total of 204 patients with ACHD were listed during the study period. The median age was 38 years, and 62.3% of the patients were listed in high urgency (HU), and 37.7% of the patients were in transplantable (T)-listing status. A total of 23.5% of the patients died or were delisted owing to clinical worsening, and 75% of the patients underwent transplantation. Median waiting time for patients with HU-listing status was 4.18 months and with T-listing status 9.07 months. There was no difference in crude mortality or delisting between patients who were HU status listed and T status listed (p=0.65). In multivariable regression analysis, markers for respiratory failure (mechanical ventilation, hazard ratio [HR]: 1.41, 95% CI: 1.11-1.81, p=0.006) and arrhythmias (anti-arrhythmic medication, HR: 1.42, 95% CI: 1.01-2.01, p=0.044) were associated with a higher risk of death or delisting. In the overall cohort, post-transplantation mortality was 26.8% after 1 year and 33.4% after 5 years. - CONCLUSIONS - Listed patients are at high risk of death without differences in the urgency of listing. Respiratory failure requiring invasive ventilation and possibly arrhythmias requiring anti-arrhythmic medication indicate worse outcomes on waiting list.
Gesehen am 11.12.2020